Closer, but No Cigar : Intergenerational Mobility across Caste Groups in India - Sinha, Rishabh (World Bank, Washington, DC, 2018)
This paper compares the intergenerational mobility of educational and occupational attainment of men from disadvantaged groups (Scheduled Castes (SC) and Scheduled Tribes (ST)) in India with the intergenerational mobility of men outside these groups during 1983-2009. Although there has been a modest convergence in mobility rates of non-SC/ST and SC/ST men in educational attainment, there has been no significant convergence in the mobility rates of occupational attainment. Upward mobility of SC/ST men remains much lower compared to non-SC/ST men. Additionally, the former are more susceptible than the latter to moving down the intergenerational ladder. The mobility gap varies over a large range across states, but the cross-state variation has declined, with convergence being higher in states with larger gaps initially. The paper finds no evidence of higher convergence in states with higher economic growth. As such, policies that focus on growth may not necessarily deliver convergence in outcomes across social groups.